Digitalization and school leadership: on the complexity of leading for digitalization in school. Issue 3 (13th March 2019) - Håkansson Lindqvist, Marcia; Pettersson, Fanny
Abstract : Purpose: Digitalization has permeated society and schools. In this process, focus has turned to the importance of school leaders in their leadership for digitalization. The purpose of this paper is to explore how school leaders understand digitalization and the digital competencies needed in leading for digitalization in Swedish schools. Design/methodology/approach: Open questions from reflective learning journals ( n =32) and interviews ( n =8) conducted with school leaders were used to explore how school leaders understand digitalization and the digital competencies needed in leading for digitalization. Findings: The findings show that school leaders see digitalization as a wide and complex concept including technical, pedagogical, administrational and organizational challenges at all levels of the school organization. Practical implications: It appears that the role of the school leader, as a complex task, has become more complex as a result of digitalization. How time, resources and professional development are made available to support school leaders in their work with leadership for digitalization in order to support teachers' and students' learning. Originality/value: This paper contributes to the area of school leadership and digitalization. The research contribution is of interest for school leaders and school organizers striving to implement and advance digitalization in schools. This also concerns the prioritization of digitalization as one of many important areas in schools as organizations.